Bukti Informal Dalam Pembelajaran Matematika - Suandito, Billy (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
Since 1945 the national education curriculum has undergone several times the changes and improvements. In 1947, 1952, 1964 and 1975 teacher-centered learning, whereas from 1984 curriculum involves students learning begin. Similarly, in the 2004 curriculum shades of constructivism learning, where students construct their own concepts or mathematical material. The 2004 curriculum continues with the Education Unit Level Curriculum (SBC) 2006. The education unit level curriculum in 2006 was replaced by Curriculum 2013. Where 2018 is expected all educational units have implemented this 2013 curriculum. Curriculum 2013 is different from the previous curriculum in teaching and learning approaches. Learning in the Curriculum 2013 using a scientific approach: to observe, ask, try, associate and communicate. In mathematics, the old paradigm of the learning process according to Locke that a child's mind as blank paper is clean and ready was often painted his teacher. Piaget said that knowledge is found, created and developed by the students. Maslow said that education is a personal interaction between students and between teachers and students. Good constructivism, RME, and the curriculum in 2013, teachers are required to make the students construct their own learning outcomes. Representation or model can appear in a variety of ways. This paper presents how a mathematical proof or material starting with the use of drawings or models, without mathematical symbols. Theorem to be proved, usually using logical symbols. At first mathematical proof is not easy. Before formally proven, starting with the learning of mathematics using informal evidence that without words, just use the image or geometry.